Specific energy consumption of material handling by excavator in the quarrying of crushed stone (Rudarsko-geološko-naftni zbornik, 2023)
A hydraulic excavator is widely used in crushed stone quarries to perform many different operations. Previous research on material handling by excavators is most often based on laboratory testing and observation of soil materials and the digging forces in them. These results are very difficult to transfer to fieldwork during the quarrying process. Therefore, in this work, the energy consumption of an excavator while working in typical materials for a crushed stone quarry was investigated. The field measurements were performed on overburden, blasted rock material, boulders, and two different crushed materials. Energy consumption was observed only during the portion of the cycle in which the bucket digs the material. In this way, the energy consumption was mainly related to the properties of the material. The highest energy consumption was found for blasted rock material, lower in overburden, and the lowest for boulders and crushed materials. These results are important for organizing an optimal distribution of machines according to the work tasks in the quarry and ultimately for energy savings.